WOODWORK TRAINING WITH LAMINATING TECHNIQUES FOR PAEDAGOGIA SLB STUDENTS - Setio, Stefanus Prabani; Putra, Heristama Anugrah; Widyastuti, Maria; Base, Flavianus Nefliando Jurney; Harianto, Johanes Kristianus; Harefa, Mei Kristiani; Renwarin, Maria Risky Pratiwi (PeKA: Jurnal Pengabdian Kepada Masyarakat, 2023)
The opportunity to practice, try and be independent is the right of all human beings. In reality, there are still human beings who find it difficult to get the opportunity to practice and develop themselves with the new skills that exist. Opportunities to get training are sometimes not considered for people with disabilities. Physical, mental and intellectual limitations become a barrier to be equal with non-disabled people. Activity limitations are not an excuse not to study and practice. Human ability has a tendency to understand a skill that is given the right method and the right practical understanding. Easy understanding, innovation in implementation methods is a solution for people with disabilities. Ability does not appear suddenly but requires assistance. The implementation of training activities for people with disabilities carried out by the community service team at SLB Paedagogia Surabaya provided a positive stimulus. The formation of an understanding of how easy it is to make a bench that has aesthetic, functional and economic value. Through the technique of lamination of plywood on curved moldings, the students understand one of the carpentry techniques. With a pedagogic approach, the application of the lamination technique by simplifying the production stage makes it easy for students with disabilities. Inherent assistance that is carried out for students with disabilities is a means of transferring knowledge.